Virtual Groups in Learning Environments: Collaboration, Cooperation or (Self) Centred Individualism? - Bradley, Sally Ann; McConnell, David (Proceedings of the International Conference on Networked Learning, 2008)
This paper argues that whilst computer mediated conferencing and virtual learning environments facilitate collaborative and cooperative learning, the actions taken by non traditional undergraduate distance learning students may not reflect the intended learning outcomes of constructivist learning. The outcome of this research has implications for the anticipated change in demographics within Higher Education in the UK and the ramifications of the Leitch Report 2006. This paper will consider the behaviour of non traditional undergraduate students engaged in task based group work whilst studying wholly online in an open access learning environment. It examines the approaches taken to achieve the task based activities. The introduction of virtual learning environments into distance education has provided the opportunity to move away from the industrial model of self instructional materials and independent study (Garrison, 1997). The internet, information technology and computer mediated conferencing has enabled collaboration and cooperation learning not previously experienced in distance education. The social environment and connectivity affords the student the opportunity to develop deeper understanding through their own constructs in dialogue with peers and tutor, students therefore have the possibility of becoming more active learners which may lead to them engaging in “deep learning” (Entwistle, 1988). The use of asynchronous computer conferencing, in principle, provides a more equal opportunity for participation in group work as participants do not need to be present at the same time (Berge & Collins, 1995). However, constructivist learning and collaborative learning require active engagement rather then passive transmission, as Mason (1992) points out interaction is not the same as participation. This small, in depth, study is based on three cohorts of Open University foundation level students, forty four participants, studying in a wholly online learning environment. Course material was delivered through the web and supported primarily through FirstClass conferencing facilities, with telephone support when appropriate. The students were aged between eighteen to post retirement, with a wide range of prior educational attainment, from no post compulsory educational qualifications to second degrees. The students engaged in a series of small, task based, group work activities throughout the duration of the eight month course. Group work was assessed through their reflection on their contribution to the activity and application of netiquette; the task output is not assessed. Findings are based on the authentic student voice, through the use of computer mediated transcripts within the online environment, student reflections and post course interviews. Participation in collaborative and cooperative learning were key elements of the course, this offers the potential to foster a culture of positive goal or reward interdependence (McConnell, 2000). It is acknowledged, however, that the loss of this independence, in respect of pace and flexibility, when students engage in collaborative distance learning is one of "the most serious disadvantages" Weller (2002, p70). The paper argues that the participants on this course approached their study from an adult learning perspective, goal, activity or learning orientated, rather than from a collaborative and constructivist learning approach. For many students their prior learning experience had been tutor/teacher led, through didactic or transmission mode. Students were, therefore, not only encountering a new pedagogical approach to learning, though constructivism, but also studying within a post modern learning environment.